2019
DOI: 10.1101/675736
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A live-cell screen for altered Erk dynamics reveals principles of proliferative control

Abstract: Complex, time-varying responses have been observed widely in cell signaling, but how specific dynamics are generated or regulated is largely unknown. One major obstacle has been that high-throughput screens for identifying pathway components are typically incompatible with the live-cell assays used to monitor dynamics. Here, we address this challenge by performing a drug screen for altered Erk signaling dynamics in primary mouse keratinocytes. We screened a library of 429 kinase inhibitors, monitoring Erk acti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(79 citation statements)
references
References 61 publications
1
78
0
Order By: Relevance
“…LOV2 can be indirectly sensitised by tuning relaxation 3 , but this compromises time-resolution. Optogenetics has a unique potential to impose or modulate complex time-encoded inputs on cellular targets, and establish long-term manipulation and mimicry of periodic and pulsatile biological phenomena 4,5 . It would be valuable to increase sensitivity while maintaining time-resolution.…”
mentioning
confidence: 99%
“…LOV2 can be indirectly sensitised by tuning relaxation 3 , but this compromises time-resolution. Optogenetics has a unique potential to impose or modulate complex time-encoded inputs on cellular targets, and establish long-term manipulation and mimicry of periodic and pulsatile biological phenomena 4,5 . It would be valuable to increase sensitivity while maintaining time-resolution.…”
mentioning
confidence: 99%
“…Rapid Ca 2+ signalling post-wounding is observed in multiple systems in vitro and in vivo (reviewed in detail in (Ghilardi et al, 2020) increased angiogenesis such as in cancer (Nicoli et al, 2007) and tuberculosis (Oehlers et al, 2015) can be analysed using this EC EKC model. This could highlight novel pathological Erk-signalling events in ECs, that could be normalised using drugs shown to modulate Erk-signalling (Goglia et al, 2020). Of note, KTR constructs for other kinases such as AKT, JNK and p38 are also now available (Regot et al, 2014;Maryu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the KTR system allows rapid quantifiable measurements of ERK activity based upon subcellular localisation of a fluorescent fusion protein, and is more sensitive to phosphatase-mediated kinase activity downregulation when compared to other commonly used kinase activity reporters. This has been applied to enable dynamic ERK-signalling pulses to be analysed in single-cell resolution both in vitro and also in vivo (Regot et al, 2014;de la Cova et al, 2017;Mayr et al, 2018;Goglia et al, 2020), where it has demonstrated to be of high utility.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of robust multicellular behaviors from heterogeneous single cell dynamics is a poorly understood, but fundamentally important phenomenon in living systems 34 committing to a specific network architecture. This model-free data-driven approach can be applied to a broad set of biological systems from synchronized beating of cardiomyocytes 35 , intercellular communication through the microenvironment 36 , brain activity 37 , molecular signaling 38 and coordinated cell migration 39 .…”
Section: Discussionmentioning
confidence: 99%